Adaptive Marketing Strategies in The Digital Era - Selly Sipakoly; Dian Ariani; Heny Herawati; I Nyoman Tri Sutaguna; Arwin Tannuary (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
In general, there are still several obstacles standing in the way of MSMEs' growth in Indonesia. The main challenge MSMEs in Majalaya District, Bandung Regency, encounter when running their enterprises is marketing. Due to the significant influence that marketing effectiveness has on corporate growth, stakeholders need to take this seriously. Additionally, MSMEs' ability to thrive is largely dependent on their brand's power to raise its market share due to the increasingly fierce competition that exists among business actors nowadays. The main objective of the program is to help MSMEs understand the principles of marketing strategy and the marketing mix. The implementation method for the counseling is using Zoom Meeting as the medium. The activity was preceded with a presentation of the questions, answers, and material. Following that, a participant's business case study was conducted, and the participants had a discussion.